Impact of Foreign Direct Investment on Economic Growth in Nepal - Parajuli, Rita (Interdisciplinary Journal of Management and Social Sciences, 2021)
Foreign Direct Investment (FDI) is an engine of economic growth. This study explains the relationship between economic growths with FDI of Nepal. The objectives of the study are to study the FDI inflows in Nepal and to analyze the impact of FDI on GDP of Nepal. The Ordinary Least Square (OLS) model has been used to examine the relationship between FDI and economic growth of Nepal. The analysis is based on data for the period of 1090/91 to 2019/20. The empirical evidence indicates that there is long run relationship between FDI and economic growth in Nepal.